Identification of maize inbreds for hybridization using agro-morphological traits and SSR markers through clustering and population structure analysis - Sneha S; SathyaSheela K.R.V; Ravikesavan R; Selvakumar T; BabuRajendraPrasad V; Sivakumar S; KumariVinothana N; Deepika V (Molecular Biology Reports, 2026)

FTIR spectroscopy and machine learning for detection of Sudan I dye as a hazardous contaminant in turmeric powder - T. Vignesh; D. Selvakumar; P.Y. Mallikarjun; N.K. Geetha; S. Madhankumar; Mandar Jatkar (Journal of Environmental Chemical Engineering, 2026)

Heavy metal contamination and ecological-health risk assessment for the sediments of a tropical coastal lake, Southwest India - Vishnu Sagar M. K.; Mirsana S.; Sabu Joseph; Selvakumar S.; Sheela A. M.; Amit Kumar (Environmental Monitoring and Assessment, 2026)

Electro-potential tuned dual-functional 2D-on-2D MXene@RGO symmetric CDI for scalable desalination and lithium-ion recovery from spent batteries - S. Lavanya; Abdul Hai; Selvakumar Palanisamy; Shadi W. Hasan; Fawzi Banat; G. Bharath (Desalination, 2026)

Biodegradation pathway and mechanism of new emerging pollutants neonicotinoids - Azhagarsamy Satheeshkumar; Ramanathan Duraimurugan; Premalakshmi Velu; Balakrishnan Muthukumar; Selvakumar Santhosh; Sandhanasamy Devanesan; Mohamad S. AlSalhi; Kuppusamy Sathishkumar; Pattanathu KSM Rahman; Aruliah Rajasekar (Journal of Environmental Sciences, 2026)

Molecular Mapping and Diversity of Fusarium Isolates Associated with Wilt and Pokkah Boeng of Sugarcane in Tropical India - R. Viswanathan; R. Selvakumar; Chandramani Raj; R. Gopi; P. Malathi; A. Ramesh Sundar; A. Annadurai; S. Balasaravanan; R. Nithyanantham; K. Kaverinathan; K. Manivannan (Sugar Tech, 2026)

Systems-Level Phosphoproteomic and RPPA Profiling Reveals Stress and DNA Damage Signalling as Early Drivers of Polymyxin B Neurotoxicity - Maytham Hussein; Thuraya Safaa Ansaf; Terry C. C. Lim Kam Sian; Mark Baker; Pouya Faridi; Zhi Ying Kho; Nivedhitha Selvakumar; Keith S. Kaye; Gauri G. Rao; Jian Li; Tony Velkov (Molecular Neurobiology, 2026)
Polymyxins remain indispensable last-line antibiotics for multidrug-resistant Gram-negative infections, yet their clinical use in central nervous system (CNS) infections is constrained by poorly understood neurotoxicity. Here, we define the early molecular signalling events underlying polymyxin B-induced CNS toxicity using an integrated phosphoproteomic and Reverse Phase Protein Array (RPPA) approach in rat brain following intracerebroventricular administration. Global phosphoproteomics revealed extensive phosphosite coverage but identified a highly selective set of significantly regulated phosphosites, implicating calcium-dependent signalling, transcriptional stress regulation, synaptic signalling, and cytoskeletal control, while parallel total proteomics showed minimal changes in protein abundance. RPPA profiling independently confirmed coordinated modulation of stress, apoptotic and survival-associated signalling pathways, including p53, CREB, SQSTM1, Bcl-2, and NFκB related nodes. Network and functional enrichment analyses converged on DNA damage signalling, apoptotic regulation and growth factor-mediated pathways as central features of the polymyxin B early neurotoxicity response, while phosphor to total protein analyses demonstrated suppression of proliferative and pro-survival signalling. Together, these data establish phosphorylation-driven signalling reprogramming as a primary early mechanism of polymyxin B-induced neurotoxicity, providing a mechanistic framework that links membrane-active antibiotic exposure to neuronal stress signalling and identifies candidate pathways for toxicity biomarkers and neuroprotective strategies.

Bioleaching assisted electrochemical reclamation of titanium from redmud using extremophilic Bacillus subtilis N3 - Punniyadharshini S; Unnamalai S; Sruthi K; Alagarsamy G; Manjima Sanil; Sankarganesh Jeyaraj; Prasana Manikanda Kartik J; Chandraraj K; Vinod Kumar Verma; Krishna Kumari V; Selvakumar R (Bioresource Technology Reports, 2025)

Radiological risk assessment of radon in groundwater of a tropical River Basin, SW India: integrating deterministic and probabilistic approaches - G. R. Anurani; S. Sukanya; Sabu Joseph; S. Selvakumar (Environmental Geochemistry and Health, 2025)

Enterobacter hormaechei mediated biodegradation of PET: a sustainable approach to plastic waste - Selvakumar Santhosh; Jayaraman Narenkumar; Kayeen Vadakkan; M. S. Nandini; Aruliah Rajasekar; Rajaram Rajamohan (Biodegradation, 2025)

Structural, Spectroscopic, and DFT Studies of N′-(2,4-difluorobenzylidene)-2-furoic Hydrazide for Electronic and Therapeutic Applications - C. Arunagiri; S. Selvakumar; S. Jeyavijayan; N. Karthik; I. Rama; A. Subashini (Journal of Fluorescence, 2025)

Effect of Carbon Nanomaterials on Soil and Plant Microbiome - Kasthuri Selvakumar; Kalaiselvi Thangavel; Senthamilselvi Dhandapani; Rajkishore S. K.; Bharani A.; Subhashini R. (Journal of Soil Science and Plant Nutrition, 2025)

Effectiveness of Mycorrhiza on Soil Enzyme Activity, Nutrient Content and Fruit Quality of Dragon Fruit in Acidic Soil Conditions - Ankita Sahu; Kundan Kishore; Upendra Kumar; G. Selvakumar; S. C. Sahoo; S. N. Dash; R. K. Nayak (Applied Fruit Science, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Corrigendum to “Advancing nanoarchitectures of 2D WO3/MXene photoanode for enhanced photoelectrocatalytic oxidation of phenol and arsenic in synthetic wastewater” [Environ. Res. 260 (2024) 119676] - G. Bharath; Selvakumar Palanisamy; T. Sivaranjani; A. Karthigeyan; S. Rajakarthihan; Fawzi Banat (Environmental Research, 2024)

Advancing nanoarchitectures of 2D WO3/MXene photoanode for enhanced photoelectrocatalytic oxidation of phenol and arsenic in synthetic wastewater - Bharath G; Selvakumar Palanisamy; Sivaranjani T; Karthigeyan A; S. Rajakarthihan; Fawzi Banat (Environmental Research, 2024)

Tackling toxicity and stability using eco-friendly metal-halide ion substituted perovskite nanocrystals for advanced display color conversion - Maithili K. Rao; M. Selvakumar; M.G. Mahesha; Selvaraj Paramasivam; M.S. Santosh; S. Senthilkumar; Shiva Kant; Sami Rtimi (Chemical Engineering Journal, 2024)

Geospatial based AHP analysis for habitat suitability of elephants and the effects of human elephant conflict in a tropical forest of Western Ghats in India - P. Vineetha; S. Sarun; S. Selvakumar; Reghunath Rajesh (European Journal of Wildlife Research, 2024)

Development of superhydrophobic/superoleophilic cotton micro dust waste functionalized SiO2 nanocomposite as an efficient adsorbent for oil/water separation - A. Dhakshana; R. Selvakumar; K. Vivekanand; M. Alagappan; K. Chandraraj; S. P. Suriyaraj (Nanotechnology for Environmental Engineering, 2024)

Evaluation of potential trace element contamination and ecological risks of beach sediments, Andaman and Nicobar Archipelago, India - S. Anbalagan; S. Krishnakumar; K. Kasilingam; Satheesh Herbert Singh; D. Pradhap; P. Saravanan; K. Neelavannan; N.S. Magesh; S. Selvakumar (Total Environment Advances, 2024)

In-grown flower-like nanoV2O5 on crumbled GO nanosheets as a high-performance catalyst for organic pollutant removal - Sahil S. Magdum; Mrunal Bhosale; Gowthami Palanisamy; Karuppaiah Selvakumar; Sadhasivam Thangarasu; Tae Hwan Oh (Journal of Water Process Engineering, 2024)

Assessment of changes in land use/land cover and land surface temperature in a fast-growing urban agglomeration of Southern India - J. B. Jibitha; A. L. Achu; Sabu Joseph; S. P. Prasood; Jobin Thomas; S. Selvakumar (Environment, Development and Sustainability, 2024)

Screening and validation of Ty-1, Ty-3 and Ty-3a specific markers in Solanum chilense accessions for resistance to tomato leaf curl virus - Muthukumar Palanisamy; Gograj Singh Jat; Pritam Kalia; Chitra Devi Pandey; Selvakumar Raman; Shilpi Kumari; Sachin Kumar; B. S. Tomar (Genetic Resources and Crop Evolution, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Environmental impact of one-step hydrothermal green synthesized ZnO nanoparticles in DI diesel engine performance analysis using duel fuel - S. Ganesan; S. lakshmisankar; Seepana Deepak; M. Selvakumar; S. P. Venkatesan; J. Hemanandh (Nanotechnology for Environmental Engineering, 2023)

Effect of gamma-ray irradiated reduced graphene oxide (rGO) on environmental health: An in-vitro and in-vivo studies - S. Sivaselvam; A. Mohankumar; R. Narmadha; R. Selvakumar; P. Sundararaj; C. Viswanathan; N. Ponpandian (Environmental Pollution, 2023)

Recent advances in consolidated bioprocessing for conversion of lignocellulosic biomass into bioethanol – A review - Selvakumar Periyasamy; J. Beula Isabel; S. Kavitha; V. Karthik; Badr A. Mohamed; Desta Getachew Gizaw; P. Sivashanmugam; Tejraj M. Aminabhavi (Chemical Engineering Journal, 2023)

Genetic diversity in Groundnut (Arachis hypogaea. L) genotypes varying in maturity duration - R. Sangeetha Vishnuprabha; PL. Viswanathan; S. Manonmani; L. Rajendran; T. Selvakumar (Vegetos, 2022)

Inheritance of purple colour and its different flavonoids profiling in F2 populations of tropical carrot (Daucus carota L.) - Raman Selvakumar; Pritam Kalia; Dalasanuru Chandregowda Manjunathagowda; R. S. Raje (Genetic Resources and Crop Evolution, 2022)

Revealing Gene Action of Different Root Pigments in Tropical Carrot (Daucus carota) - Raman Selvakumar; Pritam Kalia; R. S. Raje; Abhijit Kar (Agricultural Research, 2022)

Combined effect of nano-silica and randomly distributed fibers on the strength behavior of clay soil - P. Kulanthaivel; S. Selvakumar; B. Soundara; V. S. Kayalvizhi; S. Bhuvaneshwari (Nanotechnology for Environmental Engineering, 2022)

Epidemiology of sugarcane wilt: predisposition by root borer Polyocha depresella a myth or reality - R. Viswanathan; R. Selvakumar; N. Geetha; C. G. Balaji; A. Annadurai; Adhini S. Pazhani; P. Malathi; A. Ramesh Sundar; R. Nithiyanantham; K. Manivannan (Indian Phytopathology, 2022)

Influence of nano-silica and sodium silicate on the strength characteristics of clay soil - S. Selvakumar; P. Kulanthaivel; B. Soundara (Nanotechnology for Environmental Engineering, 2021)

Acute Traumatic Brain Injury-Induced Neuroinflammatory Response and Neurovascular Disorders in the Brain - Duraisamy Kempuraj; Mohammad Ejaz Ahmed; Govindhasamy Pushpavathi Selvakumar; Ramasamy Thangavel; Sudhanshu P. Raikwar; Smita A. Zaheer; Shankar S. Iyer; Raghav Govindarajan; Premkumar Nattanmai Chandrasekaran; Casey Burton; Donald James; Asgar Zaheer (Neurotoxicity Research, 2021)

Novel approaches on identification of conserved miRNAs for broad-spectrum Potyvirus control measures - Ramamoorthy Sankaranarayanan; Sankara Naynar Palani; Nagarajan Tamilmaran; A. S. Punitha Selvakumar; P. Chandra Sekar; Jebasingh Tennyson (Molecular Biology Reports, 2021)

Spectroscopic Studies on the Interaction of Naphthyridines with DNA and Fluorescent Detection of DNA in Agarose Gel - G. Mahalakshmi; B. Selvakumar; K.N. Vennila; P. Lakshmana Rao; S. Madhuri; M. Seenivasaperumal; Kuppanagounder P. Elango (Journal of Fluorescence, 2021)

Trends in Biological Nutrient Removal for the Treatment of Low Strength Organic Wastewaters - J Rajesh Banu; J Merrylin; S Kavitha; R Yukesh Kannah; P Selvakumar; S Gopikumar; P Sivashanmugam; Khac-Uan Do; Gopalakrishnan Kumar (Current Pollution Reports, 2021)

Structure-based design, synthesis, biological evaluation, and molecular docking of novel 10-methoxy dibenzo[b,h][1,6]naphthyridinecarboxamides - K. N. Vennila; B. Selvakumar; V. Satish; D. Sunny; S. Madhuri; K. P. Elango (Medicinal Chemistry Research, 2021)

Genome-wide association studies revealed novel stripe rust resistance QTL in barley at seedling and adult-plant stages - Sanjaya Gyawali; Sujan Mamidi; Shiaoman Chao; Subhash C. Bhardwaj; Pradeep S. Shekhawat; Rajan Selvakumar; Om P. Gangwar; Ramesh Pal Singh Verma (Euphytica, 2021)

Next Generation Precision Medicine: CRISPR-mediated Genome Editing for the Treatment of Neurodegenerative Disorders - Sudhanshu P. Raikwar; Nidhi S. Kikkeri; Ragha Sakuru; Daniyal Saeed; Haris Zahoor; Keerthivaas Premkumar; Shireen Mentor; Ramasamy Thangavel; Iuliia Dubova; Mohammad Ejaz Ahmed; Govindhasamy P. Selvakumar; Duraisamy Kempuraj; et al. (Journal of Neuroimmune Pharmacology, 2019)

Molecular Association of Glia Maturation Factor with the Autophagic Machinery in Rat Dopaminergic Neurons: a Role for Endoplasmic Reticulum Stress and MAPK Activation - Govindhasamy Pushpavathi Selvakumar; Shankar S Iyer; Duraisamy Kempuraj; Mohammad Ejaz Ahmed; Ramasamy Thangavel; Iuliia Dubova; Sudhanshu P. Raikwar; Smita Zaheer; Asgar Zaheer (Molecular Neurobiology, 2019)

Mast Cell Proteases Activate Astrocytes and Glia-Neurons and Release Interleukin-33 by Activating p38 and ERK1/2 MAPKs and NF-κB - Duraisamy Kempuraj; Ramasamy Thangavel; Gvindhasamy Pushpavathi Selvakumar; Mohammad Ejaz Ahmed; Smita Zaheer; Sudhanshu P. Raikwar; Haris Zahoor; Daniyal Saeed; Iuliia Dubova; Gema Giler; Shelby Herr; Shankar S. Iyer; et al. (Molecular Neurobiology, 2019)

Targeted Gene Editing of Glia Maturation Factor in Microglia: a Novel Alzheimer’s Disease Therapeutic Target - Sudhanshu P. Raikwar; Ramasamy Thangavel; Iuliia Dubova; Govindhasamy Pushpavathi Selvakumar; Mohammad Ejaz Ahmed; Duraisamy Kempuraj; Smita A. Zaheer; Shankar S. Iyer; Asgar Zaheer (Molecular Neurobiology, 2019)

Glia Maturation Factor Dependent Inhibition of Mitochondrial PGC-1α Triggers Oxidative Stress-Mediated Apoptosis in N27 Rat Dopaminergic Neuronal Cells - Govindhasamy Pushpavathi Selvakumar; Shankar S Iyer; Duraisamy Kempuraj; Murugesan Raju; Ramasamy Thangavel; Daniyal Saeed; Mohammad Ejaz Ahmed; Harris Zahoor; Sudhanshu P. Raikwar; Smita Zaheer; Asgar Zaheer (Molecular Neurobiology, 2018)

Salinization of shallow aquifer in the Karamaniyar river basin, Southern India - S. Selvakumar; N. Chandrasekar; S. Kaliraj; N. S. Magesh (Environment, Development and Sustainability, 2018)

Effects of Fluoride on Bone in an Animal Model of Vitamin D Deficiency - Joseph Dian Bondu; M. S. Seshadri; R. Selvakumar; Jude Joseph Fleming (Indian Journal of Clinical Biochemistry, 2017)

Mapping of coastal aquifer vulnerable zone in the south west coast of Kanyakumari, South India, using GIS-based DRASTIC model - S. Kaliraj; N. Chandrasekar; T. Simon Peter; S. Selvakumar; N. S. Magesh (Environmental Monitoring and Assessment, 2015)

Aquatic insect conservation: a molecular genetic approach - K. G. Sivaramakrishnan; S. Janarthanan; C. Selvakumar; M. Arumugam (Conservation Genetics Resources, 2014)

Effect of Biotin and Galactose Functionalized Gelatin Nanofiber Membrane on HEp-2 Cell Attachment and Cytotoxicity - R. Selvakumar; S. Nazar Mohamed Mohaideen; S. Aravindh; C. Sabarinath; M. Ananthasubramanian (The Journal of Membrane Biology, 2014)

Revealing effect of bathymetry over tsunami run-up through factor analysis - R. Selvakumar; S. M. Ramasamy (Arabian Journal of Geosciences, 2013)

Pseudomonas lurida M2RH3 (MTCC 9245), a psychrotolerant bacterium from the Uttarakhand Himalayas, solubilizes phosphate and promotes wheat seedling growth - Govindan Selvakumar; Piyush Joshi; Preeti Suyal; Pankaj K. Mishra; Gopal K. Joshi; Jaideep K. Bisht; Jagdish C. Bhatt; Hari S. Gupta (World Journal of Microbiology and Biotechnology, 2011)

Seven novel single nucleotide polymorphisms identified within river buffalo (Bubalus bubalis) lactoferrin gene - Periasamy Kathiravan; Ranjit S. Kataria; Bishnu P. Mishra; Praveen K. Dubey; M. Selvakumar; Neetu Tyagi (Tropical Animal Health and Production, 2010)

Growth promotion of wheat seedlings by Exiguobacterium acetylicum 1P (MTCC 8707) a cold tolerant bacterial strain from the Uttarakhand Himalayas - G. Selvakumar; S. Kundu; Piyush Joshi; Sehar Nazim; A. D. Gupta; H. S. Gupta (Indian Journal of Microbiology, 2010)

Control of sheath blight disease in rice by thermostable secondary metabolites of Trichothecium roseum MML003 - M. Jayaprakashvel; M. Selvakumar; K. Srinivasan; S. Ramesh; N. Mathivanan (European Journal of Plant Pathology, 2010)

Mountain Aspect Influences the Genetic Clustering of Psychrotolerant Phosphate Solubilizing Pseudomonads in the Uttarakhand Himalayas - Govindan Selvakumar; Piyush Joshi; Pankaj K. Mishra; Jaideep K. Bisht; Hari S. Gupta (Current Microbiology, 2009)

Phosphate solubilization and growth promotion by Pseudomonas fragi CS11RH1 (MTCC 8984), a psychrotolerant bacterium isolated from a high altitude Himalayan rhizosphere - Govindan Selvakumar; Piyush Joshi; Sehar Nazim; Pankaj K. Mishra; Jaideep K. Bisht; Hari S. Gupta (Biologia, 2009)

Exiguobacterium acetylicum strain 1P (MTCC 8707) a novel bacterial antagonist from the North Western Indian Himalayas - Govindan Selvakumar; Piyush Joshi; Sehar Nazim; Pankaj K. Mishra; Samaresh Kundu; Hari S. Gupta (World Journal of Microbiology and Biotechnology, 2009)

Usefulness of ferroxidase activity of ceruloplasmin in the diagnosis of Wilson’s disease - J. J. Fleming; S. Santhosh; R. Selvakumar; A. Jose; C. E. Eapen (Indian Journal of Clinical Biochemistry, 2009)

Isolation and characterization of melanin pigment from Pleurotus cystidiosus (telomorph of Antromycopsis macrocarpa) - P. Selvakumar; S. Rajasekar; K. Periasamy; N. Raaman (World Journal of Microbiology and Biotechnology, 2008)

Characterization of a cold-tolerant plant growth-promoting bacterium Pantoea dispersa 1A isolated from a sub-alpine soil in the North Western Indian Himalayas - G. Selvakumar; S. Kundu; Piyush Joshi; Sehar Nazim; A. D. Gupta; P. K. Mishra; H. S. Gupta (World Journal of Microbiology and Biotechnology, 2008)

Isolation and Characterization of Nonrhizobial Plant Growth Promoting Bacteria from Nodules of Kudzu (Pueraria thunbergiana) and Their Effect on Wheat Seedling Growth - G. Selvakumar; S. Kundu; Anand D. Gupta; Yogesh S. Shouche; Hari S. Gupta (Current Microbiology, 2008)

Inhibitory activity of pine needle tannin extracts on some agriculturally resourceful microbes - G. Selvakumar; Supradip Saha; S. Kundu (Indian Journal of Microbiology, 2007)

External quality assurance—Role of ACBI/CMC scheme - F. S. Geethanjalai; J. Fleming; S. Swaminathan; R. Selvakumar (Indian Journal of Clinical Biochemistry, 2006)

Report of a trial with lyophilised QC sera in the CMCH/ACBI EQAS programmes in India - R. Selvakumar; S. Swaminathan; J. J. Fleming (Indian Journal of Clinical Biochemistry, 2004)

Thermal modulation of pyruvate metabolism in the freshwater prawn Macrobrachium malcolmsonii: the role of lactate dehydrogenase - S. Selvakumar; P. Geraldine (Fish Physiology and Biochemistry, 2003)

Thyroid autoantibody measurement by enzyme immunoassay - D. Charles Stephen; Nihal Thomas; R. Selvakumar; M. S. Seshadri; A. S. Kanagasabapathy (Indian Journal of Clinical Biochemistry, 1997)